State Civil Apparatus Discipline Development (ASN) at the Aceh Youth and Sports Service (Study on the Implementation of Government Regulation Number 53 of 2010 concerning Civil Servant Discipline) - Armiwal, Armiwal; Suhaibah, Suhaibah (Budapest International Research and Critics University, 2022)
Discipline is a compliance with the rules, norms, standards, laws and regulations that have been determined or applied. The method used in this research is through a qualitative approach. In this study, the selection of informants used sampling with the technique ofpurposive sampling. The informants in this study consisted of 5 people, namely, the secretary of the Dispora, the Head of the Sub-department of Personnel, and 3 ordinary ASN employees. The data collection techniques used in this study were (1) interviews, (2) observations, and (3) the use of document sources and literature study. Activities in data analysis are: Condensation of data, presentation of data and drawing conclusions. Discipline development carried out by the Aceh Youth and Sports Service (DISPORA) Aceh is in the form of giving salaries at the beginning of the month, not on the 1st, can be missed if at the beginning of the month it falls on a weekend, the salary given is sent through the accounts of registered ASN . Old-age benefits are given to ASN after the ASN retires, but the retirement salary itself has a lot of correspondence that must be taken care of and it takes time. The implementation of sanctions for violations of ASN discipline at the Aceh DISPORA is only light discipline, namely in the form of verbal warnings and written warnings as well as written statements of dissatisfaction, for cases such as abuse of authority and intermediaries to gain profits do not reach the supervisory party because the supervisory party does not go into depth when there are field activities.